CONSTRUCTION OF KNOWLEDGE ONLINE: THE CASE OF SOCIAL NETWORK PROEDI - Lisbôa, Eliana Santana (2015)
Assess the construction of knowledge constitutes a challenge for educators seeking to investigate the potential that social networks offer for online education . To contribute to this debate is that we present in this article an empirical study aiming to compare the process of knowledge construction in two forums , applied in different contexts (formal and informal ) , a social network that brings together a community of language teachers Portuguese online that discuss topics related to professional development in ICT . The theoretical framework is the Theory of Online Collaborative Learning - OCL developed by Harasim (2012), as well as the concept of cognitive presence, presented by Garrison et al . (2001) to detect and evaluate the process of knowledge construction in asynchronous online interactions. The results show that there was construction of knowledge in both forums analyzed. However the forum was applied in a formal context that became more visible the more complex categories which show that the group reached higher levels of critical thinking. As advocated by OCL although modest, the results show that a social network can achieve higher levels of thinking and collaboration. The study also shows that the grid Garrison to detect cognitive presence is useful to pursue and dissect the process of knowledge construction in a social network.